PERAN IKLIM ORGANISASI DALAM MENINGKATKAN KINERJA PEGAWAI PADA BADAN PUSAT STATISTIK KABUPATEN DELI SERDANG - Viny Arilia; Sari Wulandari; Mhd. Dani Habra (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
The purpose of this study was to determine the role of organizational climate in improving employee performance at the Central Bureau of Statistics of Deli Serdang Regency. The type of method used in this research is descriptive with a qualitative approach, namely the observation process, accurate data collection based on facts found in the field, as well as interviews with resource persons. The results of the study indicate that organizational climate plays an important role in improving employee performance at the Central Statistics Agency of Deli Serdang Regency, due to the support and trust from colleagues and superiors so as to improve employee performance. This means that the role of an increasingly conducive organizational climate can improve employee performance.